Assessing Options for Effective Mechanisms to Share Benefits : Insights for REDD+ Initiatives - PricewaterhouseCoopers (Program on Forests (PROFOR), Washington, DC, 2013)
One objective of this paper is to provide information and tools for policy makers and development partners engaged in developing arrangements for transferring REDD plus benefits. This paper is also intended to help key stakeholders design a mechanism that is appropriate for a country's context. Another objective is to provide information and tools for assessing and structuring benefit sharing mechanisms at national and sub national levels (e.g., at the local government or project level) and at local community levels. This paper, however, does not address benefit sharing within communities, because this would depend on local circumstances. This paper includes an options assessment framework that will help REDD plus stakeholders identify nationally appropriate REDD plus benefit sharing mechanisms, and offers guidance on measures needed to successfully design and implement a selected mechanism. This paper is based on a quick review of 12 existing forest benefit sharing mechanisms representing a spectrum of approaches. From the 12, five were selected and examined in detail using information from key informants and available materials. This paper is divided into three sections to provide the reader with an introduction to forest sector benefit sharing mechanisms and their relevance for REDD plus; guidance on establishing benefit sharing mechanisms; and options assessment frameworks for four REDD plus benefit sharing mechanism categories.